Bersama Remaja Membangun Generasi Peduli ASI Melalui Edukasi Menyusui Sebagai Upaya Fondasi Kesehatan Reproduksi Berkelanjutan - Nurasih, Nurasih; Wahyuni, Santi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
The lack of knowledge among adolescents about exclusive breastfeeding and reproductive health is a barrier in preparing the younger generation to support breastfeeding practices in the future. This community service activity aims to improve adolescents’ knowledge, attitudes, and motivation at SMK RISE Cirebon Regency, supporting sustainable reproductive health through breastfeeding education. Held on August 1, 2025, coinciding with World Breastfeeding Week, the activity involved 66 12th-grade students, the principal, teachers, and a cross-disciplinary team of lecturers, students, and laboratory staff. An educational, promotive, and participatory approach was used through presentations, educational videos, interactive discussions, question-and-answer sessions, and pre- and post-test evaluations. The results showed a significant increase in participants’ knowledge, from an average pre-test score of 6.77 ± 2.10 to a post-test score of 10.59 ± 2.16, with the knowledge category shifting from